Self-Confidence of Students Bullying at MTsN 5 Agam - Guslinda, Guslinda; Sukmawati, Indah (Current Issues in Counseling, 2023)
Bullying is behavior or actions that hurt someone both physically and psychologically which indicate a lack or weakness of power between the bully and the bully. Bullying is becoming more frequent due to the lack of response from various parties to these actions. The impact of bullying behavior can affect all aspects of the self, one of which can reduce students' self-confidence. This research aims to describe the self-confidence of students who are victims of bullying at MTsN 5 Agam. This research uses a quantitative approach and applies descriptive methods. Sampling was carried out using total sampling technique. The subjects in this research were 61 students who were victims of bullying at MTsN 5 Agam. The data collection instrument was a student self-confidence questionnaire using a Likert scale model. Data were analyzed using descriptive statistical methods. The results showed that the self-confidence of students who were victims of bullying at MTsN 5 Agam was in the low category with a percentage of 43%, 19 students were in the medium category with a percentage of 31%, 13 students were in the high category with a percentage of 21%, and 3 students were in the very low category with a percentage of 5%. Based on these findings, guidance and counseling teachers in schools as one of the educators responsible for students can provide guidance and counseling services so that students who are victims of bullying can increase their self-confidence. Services that guidance and counseling teachers can provide to increase students' self-confidence include individual counseling services, information services, group guidance services and group counseling services.